Zonally Elongated Transient Flows: Phenomenology and Sensitivity Analysis. Issue 6 (8th June 2018) - Rudko, M. V.; Kamenkovich, I. V.; Iskadarani, M.; Mariano, A. J.
Abstract: This study explores the phenomenology of zonally elongated transients (ZELTs) in the ocean and the sensitivity of their properties to changes in several environmental factors. ZELTs explain a major part of anisotropy in mesoscale turbulent flow. Calculations are performed in a two‐layer, quasi‐geostrophic model. Empirical Orthogonal Functions (EOF) decomposition allows for the separation of ZELTs from the background turbulent flow as several leading EOF modes. The leading Extended EOF reveals that ZELTs propagate westward at the speed of ∼ 1 cm s −1 . The decrease in the planetary vorticity gradient and increase in the bottom drag coefficient each leads to flattening of the variance spectrum, isotropization of the leading EOF, and fast decay of the autocorrelation function of its corresponding Principal Component. Key Points: Anisotropy of mesoscale variability The impact of environmental parameters on oceanic anisotropy